Cell Fusion by Canine Distemper Virus-Infected Cells - Rankin, Anne M. (1972)
AV3 cells (continuous human amnion) infected with the Onderstepoort strain of canine distemper virus produced cell fusion within 2 to 5 hr when added to AV3 cell monolayers. An apparent requirement for intact, infected cells was demonstrated by showing that (i) frozen-and-thawed infected cells failed to induce fusion, (ii) infected cells frozen in the presence of glycerol retained their ability to induce fusion, (iii) infected cells subjected to swelling in hypotonic buffer and homogenization lost their ability to fuse cells, and (iv) semipurified and concentrated virus preparations with infectivity titers as high as 10(7.5) mean tissue culture doses per ml failed to induce fusion within 5 hr. Preparations of intact, infected cells had a mean log(10) ratio of infectivity to fusion activity of 3.6. Treatment with beta-propiolactone rendered the active preparations free from detectable infectivity while they retained their ability to cause cell fusion. Cycloheximide did not block the formation of syncytia in assay cells. This type of cell fusion was neutralized by canine distemper virus immune antisera, and measles virus immune sera showed a slight degree of cross-neutralization. Other cell lines, HEp-2, MA 139 (embryonic ferret lung), MA 104 (embryonic rhesus monkey kidney), and Vero (African green monkey kidney) were also susceptible.